„Rejs" jako gatunek - Hendrykowski, Marek (Przestrzenie Teorii, 2007)
Marek Piwowski's film „Rejs" (The Cruise) made in 1969 and the premiere of which was on 10 October 1970 at „Bajka" cinema in Warsaw, rightly (deserves) to be one of the most popular Polish films of all time. This study attempts to offer a more complete characterisation of the feature of the genre of this unusual work of film art. It is commonly thought that „Rejs" is a comedy. Against the background of the model of comedy of the 60s of the 20th century, however, it is a comedy of a very special kind. The author does not doubt the comedic character of Piwowski's film, but points to different possible from those used until now ways of interpreting this film (a holiday comedy, anti-production film, social satire, pamphlet, psychodrama, sociodrama), starting from the assumption that the genre instruction written into this work contains a much richer repertoire of possible interpretations.